2016
DOI: 10.1021/acsami.5b10545
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled N/S Codoped Flexible Graphene Paper for High Performance Energy Storage and Oxygen Reduction Reaction

Abstract: A novel flexible three-dimensional (3D) architecture of nitrogen and sulfur codoped graphene has been successfully synthesized via thermal treatment of a liquid crystalline graphene oxide-doping agent composition, followed by a soft self-assembly approach. The high temperature process turns the layer-by-layer assembly into a high surface area macro- and nanoporous free-standing material with different atomic configurations of graphene. The interconnected 3D network exhibits excellent charge capacitive performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 65 publications
0
56
0
Order By: Relevance
“…Carbonaceous materials are abundant and versatile, which have attracted considerable interest for basic research and practical applications in various fields due to their easy availability and diverse bonding ability to other non‐carbon atoms, especially specific structures at nano‐ and macro‐scales . The development of well‐defined porous structure in carbonaceous materials is one of the interesting areas, because the pore structure and material transformation have considerable effects on their functionalities . Heteroatoms, such as nitrogen (N), sulfur (S), phosphorus (P) and boron (B) have been introduced into the porous carbon for their unique physical and chemical properties to broaden the application of carbonaceous materials .…”
Section: Introductionmentioning
confidence: 99%
“…Carbonaceous materials are abundant and versatile, which have attracted considerable interest for basic research and practical applications in various fields due to their easy availability and diverse bonding ability to other non‐carbon atoms, especially specific structures at nano‐ and macro‐scales . The development of well‐defined porous structure in carbonaceous materials is one of the interesting areas, because the pore structure and material transformation have considerable effects on their functionalities . Heteroatoms, such as nitrogen (N), sulfur (S), phosphorus (P) and boron (B) have been introduced into the porous carbon for their unique physical and chemical properties to broaden the application of carbonaceous materials .…”
Section: Introductionmentioning
confidence: 99%
“…The S2p spectrum (Fig. 6d) established three peaks at 163.9, 165.3, and 168.5 eV, corresponding with S 2p 3/2 , S 2p 1/2 , and oxidized sulfur (-SO n -), respectively [26] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6b) indicated that the main peak at 284.8 eV was attributable to the graphitic sp 2 carbon. The other peaks at 283.9, 285.4, 286.6, and 287.2 eV were assigned to C-S, C-C, C-O, and C-N, respectively [26] . This results confirmed N and S atoms had been doped into the carbon skeletons.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, codoping graphene with two types of dopants can also greatly benefit electrochemical performance [57][58][59]. For example, a novel strategy for synthesis of highly porous nitrogen-sulfur co-doped graphene nanoribbons (NS-GNRs) with enhanced active sites was developed by Gopalsamy et al [57].…”
Section: D Graphene-based Supercapacitorsmentioning
confidence: 99%
“…Also, a novel flexible architecture of nitrogen and sulfur co-doped graphene structures was synthesized via a thermal treatment in the mixture of liquid crystalline graphene oxide and doping agents followed by a soft self-assembly approach, resulting in a high surface area macro-and nanoporous free-standing material. A good gravimetric capacitance of 305 F g −1 (at 100 mV s cycles were obtained [58]. In another approach using phosphorous (P) codopant, a phosphorus and nitrogen co-doped carbon material (PNDC) was synthesized from aminated tannin and polyphosphoric acid by a rapid and highly efficient microwave synthetic technique.…”
Section: D Graphene-based Supercapacitorsmentioning
confidence: 99%